Prevalence of carotid atherosclerosis and carotid plaque in Chinese adults: A systematic review and meta-regression analysis. (September 2018) - Song, Peige; Xia, Wei; Zhu, Yajie; Wang, Manli; Chang, Xinlei; Jin, Shuai; Wang, Jingpin; An, Lin
Abstract: Background and aims: The national representative prevalence of carotid atherosclerosis (CAS) or carotid plaque (CP) in the general Chinese population has never been estimated. We aim to generate the prevalence and number of people with CAS and CP in the general Chinese population. Methods: We searched China National Knowledge Infrastructure, Wanfang Data, VIP Database for Chinese Technical Periodical, PubMed, Embase and Medline. Articles reporting the prevalence of CAS or CP in the general Chinese population were included. A multilevel mixed-effects logistic regression was used to estimate the age- and gender-specific prevalence of CAS and CP. The effects of risk factors for CAS were assessed by a random-effects meta-analysis. Results: The prevalence of CAS and CP increased with advanced age. Males had a higher prevalence of CAS and CP than females consistently across all age groups. Overall, 27.22% and 20.15% of Chinese people aged 30–79 years were with CAS and CP, respectively, in 2010, equivalent to 207.73 million and 153.82 million affected individuals. With demographic ageing, the number of people affected by CAS and CP will increase to 267.25 million and 199.83 million, respectively, by 2020. In addition, current smoking, hypertension and diabetes were found to be risk factors for CAS. More than 70% of the national CAS cases were in rural China in 2010. Conclusions: CAS and CP are highly prevalent in China. The huge disease burden of CAS and CP calls for efforts on effective preventive health strategies and early-detection of CVDs in people with CAS or CP, especially in rural areas. Highlights: The prevalence of carotid atherosclerosis and carotid plaque increases with age and is higher in males than in females. Advanced age, male gender, current smoking, hypertension and diabetes are risk factors for carotid atherosclerosis. The disease burden of carotid atherosclerosis is considerably higher in rural China than in urban China.